Estudo da dinâmica de bolhas de gás isoladas em um rotor centrífugo - Silva, Higor Leandro Veiga da (2019)
Electrical submersible pump using centrifugal pumps is currently one of the most commonly used artificial lifting techniques in the oil industry. However due to the presence of gas in some oil reservoirs, pumps can operate with two-phase flow. In this case, the presence of gas in the pump impeller channels may cause performance degradation, reducing its lift capacity, as centrifugal pumps are design to operate with single-phase flow. Due to the presence of the twophase flow and to the complexity of a pump geometry, the majority of the studies related to centrifugal pumps aims on the evaluation of the overall pump performance for different operational conditions, such as varying gas fraction, rotor rotating speed and pump intake pressure. Also due to the high rotating speeds, there are only a few studies on the visualization of the two-phase flow in centrifugal pumps. This scenario, in the present work a numerical and experimental study on the flow of isolated gas bubbles in the centrifugal pump impeller channels is develop. The experimental evaluation of the flow was performed using an experimental setup built at the NUEM-UTFPR. The bench is fabricated with a transparent polycarbonate material that allows the visualization of the flow through the impeller channels. A camera attached to the rotor shaft is used to acquire images of the flow in a rotary frame of reference. From the images acquired by the camera, the velocity, displacement and bubble diameters were measured for different operational conditions (liquid flow rate, rotating speeds and bubble diameter). As this study concentrates on the observation of isolated bubbles, it can be considerate that the gas phase does not interfere with the liquid phase, só a single phase flow simulation of the flow was performed using the ANSYS CFX software. , for the purpose of obtaining details of the velocity and pressure fields of the liquid phase in the pump’s impeller channels. From the numerical and experimental data acquired, a correlation for the drag coefficient of a gas bubble flowing inside a centrifugal rotor under different operational conditions was developed.